Student's Digital Literacy and an Evaluation of Awareness of Ethics, Privacy, and Online Safety - Fathir Fathir; Siti Mutmainah; Teguh Ansyor Lorosae (Jurnal Pendidikan Terapan, 2026)
Purpose The development of digital technology has become an integral part of teenagers’ lives; digital technology not only presents opportunities but also poses challenges. Digital literacy is a crucial and key aspect in ensuring that students can use technology wisely and responsibly. This study aims to identify digital literacy among teenagers, with a focus on online ethics, privacy, and security. Methods The method used was a quantitative approach to measure the correlation between frequency and digital literacy among adolescents. Data was collected using a Google Forms questionnaire, which yielded responses from 105 participants. Findings The analysis results show that the majority of students have a moderate level of digital literacy (79%), while only a small proportion have a high level of digital literacy (18%). Research Implications The analysis results indicate a significant positive correlation between the frequency of internet use and the level of digital literacy, as well as between the frequency of internet use and the ability to distinguish between valid and invalid content. Originality There was also a relationship between frequency of internet use and difficulty distinguishing between true and false information.